Vivipary in coastal cacti: a potential reproductive strategy in halophytic environments - Cota-Sánchez, J. Hugo; Reyes-Olivas, Álvaro; Sánchez-Soto, Bardo (American journal of botany, 2007)
Vivipary, the germination of seeds within the fruit prior to abscission from the maternal plant, is an important event in plants. Two main types of vivipary are known in vascular plants: true vivipary and pseudovivipary. In crop grasses, pseudovivipary is an undesirable character as it results in lower yields. To date, vivipary in the Cactaceae has been reported for less than 20 species, most of which are cultivated. Here, we report viviparous (cryptoviviparous--a subcategory of true vivipary) cacti in nature in members of the tribes Cacteae and Pachycereeae (subfamily Cactoideae). We present four species inhabiting coastal plains in areas subject to periodic flooding, namely, Ferocactus herrerae, Stenocereus alamosensis, S. thurberi, and Pachycereus schottii. These species from localities in northwestern Mexico had viviparous fruits and offspring in different stages of development. A potential trend in the data indicates that the overall proportion of viviparous plants is higher in coastal flooding areas relative to halophytic, nonflooding areas. In our view, vivipary is a reproductive strategy that has evolved to provide a more efficient mechanism favoring germination and new avenues for survival by contributing to population maintenance and short-distance dispersal on halophytic substrates.